Peculiarities of tourism and recreational activities in Ukraine - Prokofiev, Olexiy (Запоріжжя: НБ ТДАТУ, 2025)
The main requirements for the organization of recreational and tourist activities are set out in our legislation. Thus, the Law of Ukraine “On the Nature Reserve Fund of Ukraine” defines the possibilities and restrictions for the organization of recreation and tourism depending on the categories of territories and objects of the nature reserve fund (hereinafter referred to as the NRF). For example, tourism is prohibited in nature reserves and protected areas of national natural, biosphere reserves and regional landscape parks.
Keywords: recreational and tourist activities; tourism; local governments